2006
DOI: 10.1002/chem.200501480
|View full text |Cite
|
Sign up to set email alerts
|

Side Chain Mediated Electronic Contact between a Tetrahydro‐4H‐thiopyran‐4‐ylidene‐Appended Polythiophene and CdTe Quantum Dots

Abstract: Currently, many watershed models are available that have various complexities, strengths, and weaknesses. The basic mathematical foundations of these mathematical models are often overlooked due to high demands on convenient applications with graphical user interfaces. Although this and other factors are important while selecting a model, the mathematical foundation should also be taken into account, as performance or efficiency and accuracy of a model depend on its simplicity or complexity. A comprehensive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…In another approach, both poly(thiophene)s and nanocrystals are functionalized with special groups capable of strongly interacting with each other. 7 In this case, enhanced macromolecule-nanocrystal interactions efficiently impede the phase separation. 8,9 Molecular composites of diaminopyrimidine side-functionalized poly(hexylthiophene)s and mercaptoalkylthymine capped CdSe nanocrystals can be considered as an instructive example of this approach in the preparation and processing of hybrid materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another approach, both poly(thiophene)s and nanocrystals are functionalized with special groups capable of strongly interacting with each other. 7 In this case, enhanced macromolecule-nanocrystal interactions efficiently impede the phase separation. 8,9 Molecular composites of diaminopyrimidine side-functionalized poly(hexylthiophene)s and mercaptoalkylthymine capped CdSe nanocrystals can be considered as an instructive example of this approach in the preparation and processing of hybrid materials.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there exist very few published examples of this type of nanocomposites. In the first case tetrahydro-4H-thiopyran-4-ylidene-functionalized polythiophene was blended with CdTe nanocrystals, 7 in the second one polythiophene polymer chains with pendant carbodithioate complexing groups were blended with CdSe nanoparticles. 19 Carboxylic groups are popular nanocrystals 0 capping ligands.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that various stabilizers or capping/self-assembling chemicals were attempted to improve the property of the CdTe quantum dots, including thiol-containing chemicals or polymers, [10][11][12][13][14][15] amine-containing chemicals or polymers, [16][17][18] polystyrene, 19 calix [4]arene, 20 bovine serum albumin, 21,22 liposome complexes 23 and positively charged stabilizers. 24 The introductions of these ligands onto nanoparticle surfaces provide not only the stability of these nanoentities in different solvents, but also the desired surface functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, devices made of PSBTBT‐NH 2 , modified by end‐capping with mono‐aniline, blended with CdTe tetrapods show significant improvement in performance compared to that made of non‐modified PSBTBT blends under BDT solvent–vapor annealing ( V oc = 0.76 V, J sc = 5.11 mA cm − 2 , FF = 0.41, and PCE = 1.59%), as shown in Figure 4a. Evidently, the presence of the mono‐aniline functional group effectively provides intimate contact between the polymer and CdTe NCs through covalent interactions,15, 22–24 which is encouraging for application in the HSCs.…”
mentioning
confidence: 98%
“…For better interaction, a number of factors, including the NCs' size and shape,9, 12, 16 thermal annealing,11–18 solvent–vapor annealing,14, 20 as well as directly grafting a conjugated polymer onto quantum dots,21 have been identified experimentally as significantly affecting the nanometer‐scale morphology. Recently, a new strategy for improving the compatibility between NCs and conjugated polymers was reported by functionalizing the polymers with substituents either as terminal or as side groups capable of binding to the NC's surface 15, 22–24…”
mentioning
confidence: 99%